Validation of a scale for assessing attitudes towards outcomes of genetic cancer testing among primary care providers and breast specialists. - Anne-Deborah Bouhnik; Khadim N'Diaye; D Gareth Evans; Hilary Harris; Aad Tibben; Christi van Asperen; Joerg Schmidtke; Irmgard Nippert; Julien Mancini; Claire Julian-Reynier (PLoS ONE)
Objective To develop a generic scale for assessing attitudes towards genetic testing and to psychometrically assess these attitudes in the context of BRCA1/2 among a sample of French general practitioners, breast specialists and gyneco-obstetricians. Study design and setting Nested within the questionnaire developed for the European InCRisC (International Cancer Risk Communication Study) project were 14 items assessing expected benefits (8 items) and drawbacks (6 items) of the process of breast/ovarian genetic cancer testing (BRCA1/2). Another item assessed agreement with the statement that, overall, the expected health benefits of BRCA1/2 testing exceeded its drawbacks, thereby justifying its prescription. The questionnaire was mailed to a sample of 1,852 French doctors. Of these, 182 breast specialists, 275 general practitioners and 294 gyneco-obstetricians completed and returned the questionnaire to the research team. Principal Component Analysis, Cronbach's α coefficient, and Pearson's correlation coefficients were used in the statistical analyses of collected data. Results Three dimensions emerged from the respondents' responses, and were classified under the headings: "Anxiety, Conflict and Discrimination", "Risk Information", and "Prevention and Surveillance". Cronbach's α coefficient for the 3 dimensions was 0.79, 0.76 and 0.62, respectively, and each dimension exhibited strong correlation with the overall indicator of agreement (criterion validity). Conclusions The validation process of the 15 items regarding BRCA1/2 testing revealed satisfactory psychometric properties for the creation of a new scale entitled the Attitudes Towards Genetic Testing for BRCA1/2 (ATGT-BRCA1/2) Scale. Further testing is required to confirm the validity of this tool which could be used generically in other genetic contexts.